Maize ear growth is stimulated at the fourth day after pollination by cell wall remodeling and changes in lipid and hormone signaling. (8th April 2022) - Du, Kang; Zhao, Wenqing; Mao, Yu; Lv, Zhiwei; Khattak, Wajid Ali; Ali, Saif; Zhou, Zhiguo; Wang, Youhua
Abstract: BACKGROUND: Stimulating maize ear development is an effective way of improving yield. However, limited information is available regarding the regulation of sink strength change from weak to strong at the same position of maize plants. Here, a novel method for stimulating development combined with physiological assays and proteomics was applied to explore the regulation of ear strengthened development. RESULTS: By blocking pollination of the upper ear of maize hybrid Suyu 41, the adjacent lower ear was dramatically stimulated at 4 days after pollination (DAP). Tandem mass tag (TMT)‐based proteomics identified 173 differentially expressed proteins (fold change >1.2 or <0.83, P < 0.05) from 7793 total proteins. Gene ontology annotations indicated that several pathways showed noticeable changes, with a preferential distribution to cell wall remodeling, hormone signals and lipid metabolism in the stimulated kernels. Cell wall remodeling was highly mediated by chitinase, exhydrolase II and xyloglucan enotransglucosylase/hydrolase, and accompanied by increased sucrose and glucose content. A series of lipoxygenase proteins were significantly upregulated, causing a significant alteration in lipid metabolism. Hormone signals were influenced by the expression of the proteins involved in indole‐3‐acetic acid (IAA) transport, zeatin (ZT) biosynthesis and abscisic acid (ABA) signal response, and increased IAA, ZT and ABA content. CONCLUSION: The critical time for understanding the mechanism by which ear growth is stimulated is 4 DAP. Comparative proteomics and physiological analysis revealed that lipid metabolism enhancement, cell wall remodeling and changes in hormone signaling (IAA, ZT and ABA) were all important in stimulating early ear development. Proper regulation of these pathways may improve ear development, resulting in increased maize yield. © 2022 Society of Chemical Industry.